QUR'ANIC VERSES ON MANAGEMENT COMMUNICATION IN ISLAMIC PERSPECTIVE - Asri Yuni Vika Sari; Abd Rahman; Iwan Setiawan; Abdul Muin Bahaf (Media Inovasi Pendidikan dan Pembelajaran, 2023)
Communication as an important means in educational management activities. Communication has a major influence on the continuation of human life, in the Islamic view communication is moral al karimah or ethical, which means communication based on the Quran and Hadith (Sunnah of the Prophet). The purpose of writing this paper is to determine the communication process, the role of communication in education management and factors that affect fluency in communication sourced from verses of the Quran. The method used in this paper is qualitative, the author explores in-depth information about Islamic education communication management. The approach used is a literature study, the author gets information sourced from books and journals. The role of communication in education management includes; as a source of educational information, as a controller and coordination, as planning and achieving goals and as an increase in motivation. Keywords: communication management, communication Islamic perspective